The Relationship between Learning Agility and Work Engagement on Organizational Commitment among the Strawberry Generation - Jocelyn Patricia; Marchelina Febe Sumbaga (Fenomena, 2024)
In the industrial world, organizational success in the VUCA era hinges on employee commitment, yet the "strawberry generation" (Generations Y and Z) is often perceived as lacking fortitude, posing a significant human resource challenge. While previous studies have explored partial relationships between learning agility, work engagement, and commitment, a critical research gap exists in examining their simultaneous impact on this specific demographic within the Indonesian context. This study aims to address this gap by investigating the relationship between learning agility, work engagement, and organizational commitment among 420 strawberry generation employees in Jakarta. A quantitative correlational design with purposive sampling was employed, utilizing the Learning Agility Assessment, UWES-9, and OCQ instruments. Data were analyzed using multiple linear regression. The novelty of this research lies in its finding that both learning agility and work engagement have a significant positive relationship with organizational commitment (p < 0.05), both partially and simultaneously. This study concludes that fostering these internal competencies is a crucial strategy for enhancing the loyalty of the younger workforce. This provides a new framework for managing a generation often misunderstood, contributing a fresh perspective to organizational psychology. Di Dunia industri, keberhasilan organisasi di era VUCA bergantung pada komitmen karyawan, namun "generasi stroberi" (Generasi Y dan Z) sering dipersepsikan kurang memiliki ketahanan, yang menjadi tantangan sumber daya manusia yang signifikan. Meskipun studi sebelumnya telah mengeksplorasi hubungan antara variabel-variabel ini secara parsial, terdapat celah penelitian yang kritis dalam menguji dampak simultan keduanya pada demografi spesifik ini dalam konteks Indonesia. Penelitian ini bertujuan untuk mengisi celah tersebut dengan menyelidiki hubungan antara learning agility, work engagement, dan komitmen organisasi pada 420 karyawan generasi stroberi di Jakarta. Desain kuantitatif korelasional dengan purposive sampling digunakan, memanfaatkan instrumen Learning Agility Assessment, UWES-9, dan OCQ. Data dianalisis menggunakan regresi linear berganda. Kebaruan penelitian ini terletak pada temuannya bahwa learning agility dan work engagement memiliki hubungan positif yang signifikan dengan komitmen organisasi (p < 0,05), baik secara parsial maupun simultan. Studi ini menyimpulkan bahwa membina kompetensi internal ini adalah strategi krusial untuk meningkatkan loyalitas angkatan kerja muda. Hal ini memberikan kerangka kerja baru untuk mengelola generasi yang sering disalahpahami, serta menyumbangkan perspektif baru bagi psikologi organisasi.